Clinical impact of low bone mineral density in patients with colorectal cancer liver metastasis undergoing hepatectomy - Yuichi Aoki; Atsushi Miki; Yasunaru Sakuma; Jun Watanabe; Takehiro Kagaya; Makiko Tahara; Takumi Teratani; Kazuhiro Endo; Hideki Sasanuma; Wataru Nishimura; Hisanaga Horie; Joji Kitayama; et al. (PLoS ONE, 2025)
Background This study aimed to elucidate the clinical impact of osteopenia on the recurrence of colon cancer liver metastases. Methods Patients with colon cancer liver metastases (N = 186) undergoing hepatectomy at Jichi Medical University Hospital between March 2006 and March 2020 were examined retrospectively. Computed tomography (CT) scans on the 11th vertebra within 3 months of surgery assessed bone mineral density (BMD). Age-adjusted BMD determined osteopenia presence. Kaplan-Meier method with a log-rank test estimated survival. Factors associated with survival were assessed using Cox’s proportional hazards model after adjustment for confounders. Results Patients with osteopenia had shorter overall (p = 0.0001; 5-year overall survival, 51.8% vs 81.8%) and recurrence-free survival (p = 0.0008, 5-year recurrence-free survival: 26.3% vs 51.5%) than BMD-normal patients. In multivariable analysis, the risk factor for overall survival was osteopenia (Hazard ratio (HR) 3.79, 95% confidence interval (CI) 2.09–6.87, p = 0.001). Risk factors for recurrence were chemotherapy (HR 1.92, 95%CI 1.12–3.30, p = 0.002), tumor number (HR 1.51, 95%CI 1.02–2.27, p = 0.04), and osteopenia (HR 2.18, 95%CI 1.46–3.24 p = 0.001). Patients with osteopenia are more likely to develop lung metastases, and BMD-value reduction associated with KRAS mutation. Conclusion Osteopenia may have prognostic significance in patients with liver metastases colorectal cancer.